COUNTERING DISINFORMATION: SPAIN’S PUBLIC DIPLOMACY IN PROTECTING NATIONAL SECURITY - Tuyakbay, Sabina (Farabi Journal of Social Sciences, 2026)
Purpose. This article examines Spain’s public diplomacy measures aimed at countering disinformation and safeguarding national security. It critically assesses whether Spain’s current reliance on state-led institutions, multilateral cooperation, and civil society initiatives is adequate for addressing contemporary foreign information manipulation and interference (FIMI). Design/methodology/approach. The study employs a qualitative research design based on document and policy analysis of open-access empirical reports, national strategic documents, and peer-reviewed literature published between 2017 and 2025. The methodology includes triangulation of public opinion survey data and a comparative evaluation of institutional responses. In addition, two descriptive quantitative techniques—trend comparison and cross-national benchmarking—are applied using publicly available survey indicators. Findings. The findings indicate that disinformation represents a major concern for Spanish society, with approximately 70–83% of respondents identifying it as a significant threat, depending on the year and data source. While Spain demonstrates a degree of domestic resilience through established public diplomacy mechanisms, persistent vulnerabilities remain. These vulnerabilities are intensified by social media dynamics, AI-enhanced disinformation, and crisis-driven amplification effects. Existing tools show strengths in detection and awareness-raising but face limitations related to the speed of strategic communication, regulatory clarity, and long-term investment in digital literacy. Originality. The article contributes to the literature on public diplomacy and national security by providing a comprehensive, up-to-date assessment of Spain’s counter-disinformation framework. By integrating institutional analysis with public opinion data and cross-national benchmarks, the study offers a nuanced evaluation of public diplomacy effectiveness in the context of evolving information threats. Key words: Public diplomacy, misinformation, national security, information disorder.